1964
DOI: 10.1007/bf02663959
|View full text |Cite
|
Sign up to set email alerts
|

A study of methods for evaluation of the stability of fats and shortenings

Abstract: The data from several laboratory tests [Active Oxygen Method (AOM), modified ASTM bomb, modified ASTM bomb with catalyst added to the fat, a manometric method and an accelerated oven test] were compared with data from a storage test at 85F evaluated organoleptically at selected intervals. Tests were carried out on lard, hydrogenated vegetable oil and tallow, with and without added monoglyceride, and with and without selected antioxidants. A comparison of the data from the laboratory tests with that from the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1968
1968
1994
1994

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…and automated or modified A.O.M. methods conducted at temperatures of 100~ or higher (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) with peroxide values (PV) of 50 and above as the endpoints, deMan and deMan (22) reported that the PV at A.O.M. endpoints for L E A R and corn oil were 95 and 225 meq/kg, respectively.…”
mentioning
confidence: 99%
“…and automated or modified A.O.M. methods conducted at temperatures of 100~ or higher (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) with peroxide values (PV) of 50 and above as the endpoints, deMan and deMan (22) reported that the PV at A.O.M. endpoints for L E A R and corn oil were 95 and 225 meq/kg, respectively.…”
mentioning
confidence: 99%
“…The Schaal oven test is often used for stability testing, and it is based on organoleptic evaluation of products after accelerated storage. Several attempts have been made (1,2,8,11,12) to correlate results from the oxygen bomb, AOM, and Schaal oven tests, often with conflicting results. The AOM end point is determined as the time to reach 100 milliequivalents per Kg (13) when the sample is maintained at 97.8 C, with a constant air flow through the sample 2.33 ml/sec.…”
Section: Comparison Of Oxygen Bomb Test Results With Other Methodsmentioning
confidence: 99%
“…evaluate edible oil quality and stability. Some present methods are the amount of pentane released to the package head space by an oil (10), the active oxygen method (AOM) (11), and the oxygen bomb (12), a method which correlates well with AOM but is faster.…”
Section: Introductionmentioning
confidence: 99%